2004
DOI: 10.1103/physreve.69.016112
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory epidemic prevalence in growing scale-free networks

Abstract: We study the persistent epidemic prevalence with oscillatory behavior and the extinction of computer viruses via e-mails on a contact relational network growing with new users, for which scale-free structure is estimated from real data. Typical oscillatory phenomenon is simulated in a stochastic model for the execution and detection of viruses. The conditions of extinction by random and targeted immunizations for hubs are derived through bifurcation analysis for simpler deterministic models by using a mean-fie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 14 publications
2
54
0
Order By: Relevance
“…For example, it is found that for a linearly growing network, the evolution of the number of the infected nodes has oscillatory behaviors when the susceptible-infected-recovered (SIR) model is adopted [16]. An adaptive mechanism is studied in [17], where a susceptible individual may avoid the contacts with his infected neighbors and rewire these contacts to other susceptible individuals.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is found that for a linearly growing network, the evolution of the number of the infected nodes has oscillatory behaviors when the susceptible-infected-recovered (SIR) model is adopted [16]. An adaptive mechanism is studied in [17], where a susceptible individual may avoid the contacts with his infected neighbors and rewire these contacts to other susceptible individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Both works were analytical, without studying any real graphs. Hayashi et al [2003] study the case of a growing network and derive analytical formulas for such power-law networks (no rewiring). They introduce and study the SHIR model (susceptible, hidden, infectious, recovered), to model computers under email virus attack and derive the conditions for extinction under random and under targeted immunization, always for power-law graphs with no rewiring.…”
Section: Immunizationmentioning
confidence: 99%
“…Not only their topological features, but also their dynamical properties have been clarified. For example, it has been revealed that the scale-free structure has large influence on dynamics in its heterogeneous structure [5,6,7]. It has been shown that the epidemic threshold vanishes if their degree distributions have a power-law form, P (k) ∼ k −γ , where the characteristic degree exponent γ is lower than 3 [5].…”
Section: Introductionmentioning
confidence: 99%